Learning Curve and Associated Morbidity of Minimally Invasive Esophagectomy: A Retrospective Multicenter Study. Issue 1 (January 2019) - van Workum, Frans; Stenstra, Marianne H. B. C.; Berkelmans, Gijs H. K.; Slaman, Annelijn E.; van Berge Henegouwen, Mark I.; Gisbertz, Suzanne S.; van den Wildenberg, Frits J. H.; Polat, Fatih; Irino, Tomoyuki; Nilsson, Magnus; Nieuwenhuijzen, Grard A. P.; Luyer, Misha D.; et al.
Abstract : Objective: To investigate the morbidity that is associated with the learning curve of minimally invasive esophagectomy. Background: Although learning curves have been described, it is currently unknown how much extra morbidity is associated with the learning curve of technically challenging surgical procedures. Methods: Prospectively collected data were retrospectively analyzed of all consecutive patients undergoing minimally invasive Ivor Lewis esophagectomy in 4 European expert centers. The primary outcome parameter was anastomotic leakage. Secondary outcome parameters were operative time and textbook outcome ("optimal outcome"). Learning curves were plotted using weighted moving average and CUSUM analysis was used to determine after how many cases the plateau was reached. Learning associated morbidity was calculated with area under the curve analysis. Results: This study included 646 patients. Three of the 4 hospitals reached the plateau of 8% anastomotic leakage. The length of the learning curve was 119 cases. The mean incidence of anastomotic leakage decreased from 18.8% during the learning phase to 4.5% after the plateau had been reached ( P < 0.001). Thirty-six extra patients (10.1% of all patients operated on during the learning curve) experienced learning associated anastomotic leakage, that could have been avoided if patients were operated by surgeons who had completed the learning curve. The incidence of textbook outcome increased from 28% to 53% and the mean operative time decreased from 344 minutes to 270 minutes. Conclusions: A considerable number of 36 extra patients (10.1%) experienced learning associated anastomotic leakage. More research is urgently needed to investigate how learning associated morbidity can be reduced to increase patient safety during learning curves.